Brief Report: Ultrasonographic Assessment of Salivary Gland Response to Rituximab in Primary Sjögren's Syndrome. Issue 6 (June 2015) - Jousse‐Joulin, Sandrine; Devauchelle‐Pensec, Valérie; Cornec, Divi; Marhadour, Thierry; Bressollette, Luc; Gestin, Simon; Pers, Jacques Olivier; Nowak, Emmanuel; Saraux, Alain
<x xml:space="preserve">Abstract</x> Objective To evaluate changes in salivary gland echostructure and vascularization after rituximab treatment in patients with primary Sjögren's syndrome (SS). Methods Twenty‐eight patients with primary SS included in the multicenter, randomized, double‐blind, placebo‐controlled Tolerance and Efficacy of Rituximab in Primary Sjögren's Syndrome (TEARS) trial underwent salivary gland ultrasonography before the first placebo or rituximab infusion and then 6 months later. Trial inclusion criteria were scores of ≥50 mm on at least 2 of 4 visual analog scales (VAS) evaluating dryness, pain, fatigue, and global disease; and recent‐onset (<10 years) biologically active primary SS and/or systemic primary SS. Patients were randomly assigned (1:1) to rituximab (1 gm at weeks 0 and 2) or placebo. Ultrasonography of both parotid and submandibular glands was performed to assess echostructure (using a semiquantitative score of 0–4, with improvement defined as a ≥1‐point decrease), size of each gland, and vascularization based on the resistive index of the transverse facial artery of the parotid gland before and after lemon juice stimulation. Results Of the 28 patients, 5 (18%; 3 in the placebo group and 2 in the rituximab group) had clinically detectable bilateral parotid gland enlargement at baseline. Parotid parenchyma echostructure improved in 50% of the rituximab‐treated patients versus 7% of the placebo‐treated patients (P = 0.03). In the submandibular glands, echostructure also improved in a larger proportion of rituximab‐treated patients, although the difference was not significant (36% versus 7% of placebo‐treated patients; P = 0.16). Gland sizes and resistive index remained unchanged. Conclusion Ultrasonography showed improved salivary gland echostructure in patients with primary SS receiving rituximab, with no changes in salivary gland size or vascularization, 6 months after the first infusion.